Fatwa sebagai perantara dakwah kepada orang bukan Islam - Ibtisam Ibrahim
Methodology of da 'wah is instument in da 'wah. Meanwhile, fatwa is considered as one of the important elements that contributes to the development of Islam. However, research regarding the relationship between fatwa and da 'wah is still insufficient. Therefore in this study has been carried out because the society today seem to make their contention and ridiculed to the fatwa issued by the mufti. These issues also affect to the credibility of mufti and authority these fatwas issued. Indirectly, this will have an impact on the methodology of da 'wah towards non-Muslims. This study aims to identify the extents to fatwa can be used as a medium of da 'wah towards non-Muslims and this study underlined of three main objectives. The first is to identify the concept of fatwa from the Islamic perspective. The second objective i to clarify the concept of da 'wah towards non-Muslims. Third is to analyze fatwa as a medium of da 'wah towards non-Muslims. For achieve these objectives, the study used qualitative method. This study used exploratory study as research design. The data collected by using library research and structured interviews. Library research method was had based used to obtain data related to the concept of fatwa and da 'wah. In addition, structured interviews conducted to get the authoritative experts views related to fatwa as a medium of da 'wah towards non-Muslims. Then, the data collected were analyzed by using content analysis method. As a result, the study has found that fatwa is one of the important elements in the legal clarification since the time of Rasulullah p.b.u.h until nowadays. In addition, the concept methodology of da 'wah consists metode al¬hikmah, metode al-maw 'izah al-hasanah and metode al-mujiidalah are suitable to associated in medium da 'wah towards non-Muslim. The study also has found the combination between fatwa and da 'wah are suitable elements to approach non¬Muslims. Particularly, it refers to the fatwa process and the role of mufti. The final discussion stated that fatwa is an instrument that can be applied in da 'wah nowadays. The use methods of da 'wah is also suitable to be applied by a mufti as a means to approach the non-Muslims through their fatwa. In addition, this study contributes for the improvement and gave implications to the fatwa and da 'wah institution.